Site Directed Mutagenesis of Schizosaccharomyces pombe Glutathione Synthetase Produces an Enzyme with Homoglutathione Synthetase Activity - Dworeck, Tamara (Public Library of Science, 2012)
Three different His-tagged, mutant forms of the fission yeast glutathione synthetase (GSH2) were derived by site-directed mutagenesis. The mutant and wild-type enzymes were expressed in E. coli DH5α and affinity purified in a two-step procedure. Analysis of enzyme activity showed that it was possible to shift the substrate specificity of GSH2 from Gly (k(m) 0,19; wild-type) to β-Ala or Ser. One mutation (substitution of Ile471, Cy472 to Met and Val and Ala 485 and Thr486 to Leu and Pro) increased the affinity of GSH2 for β-Ala (k(m) 0,07) and lowered the affinity for Gly (k(m) 0,83), which is a characteristic of the enzyme homoglutathione synthetase found in plants. Substitution of Ala485 and Thr486 to Leu and Pro only, increased instead the affinity of GSH2 for Ser (k(m) 0,23) as a substrate, while affinity to Gly was preserved (k(m) 0,12). This provides a new biosynthetic pathway for hydroxymethyl glutathione, which is known to be synthesized from glutathione and Ser in a reaction catalysed by carboxypeptidase Y. The reported findings provide further insight into how specific amino acids positioned in the GSH2 active site facilitate the recognition of different amino acid substrates, furthermore they support the evolutionary theory that homoglutathione synthetase evolved from glutathione synthetase by a single gene duplication event.